A geographic information system using Google Maps for schistosomiasis survey data - Potrano, John Paul S.; Catane, Leo Anthony T.; Diaz, Lyka Cristina T.; Velasco, Lemuel Clark P. (2015)
Schistosomiasis is a parasitic disease that leads to chronic illness. Schistosomiasis survey data from four barangays of Slavador, Lanao del Norte, Philippines were stored, mapped and visualized in this study. A geographic information system (GIS) was developed in order to aid the municipal health office of Salveador in determining appropriate interventions and action plans to increase the community's compliance to mass drug administration. A database was designed through requirements analysis of Schistosomiasis survey data. A user interface that caters to the management of these data was also developed and integrated with the mapping model utilizing the Google Maps API. Lastly, a visualization model utilizing heatmaps and markers are integrated into the system.
Keywords: Parasitic diseases; Geographic information sytems